Field performance evaluation of various crystalline silicon photovoltaic technologies in Pingshan, China - Cao Yu; Jing Chai; Shuwei Han; Zi Liu; Xiaobo Li; Jianxi Yao (Energy Reports, 2019)
The field performance of three different crystalline silicon photovoltaic (PV) module technologies in Pingshan, China (BSk climate based on the Köppen-Geiger climate classification) is analyzed and compared, including p-type multicrytalline silicon (multi-Si), p-type monocrystalline silicon (mono-Si) and n-type mono-Si modules. Both p-type multi-Si and mono-Si solar cells are of the conventional type with back-surface field, whereas the n-type device is of the heterojunction (HET) type. From January 2017 to December 2018, the n-type HET modules showed the best field performance (in terms of kWh/kWp) with an average daily energy yield of 3.9 kWh/kWp. The p-type multi-Si and mono-Si modules performed similarly with an average daily energy yield of 3.7 kWh/kWp (marginally better for multi-Si modules). On-site measurements also showed that the location has a "blue-rich" and "red-rich" spectrum in the summer and winter, respectively. In general, the spectral effect is positive in the summer, and negative in the winter, for all three investigated c-Si PV technologies. Besides, the spectral effect slightly favors the HET technology in the summer, but the opposite is true for mono-Si and multi-Si devices in the winter.
Keywords: 330; Crystalline silicon; Energy yield; Field performance; Photovoltaics; Spectral mismatch